Gdańsk - Wrzeszcz ul. Grunwaldzka 54-58 / foto Karol Nowaliński. - Nowaliński, Karol (1935- ). (1980)
Przedstawia kamienice przy ul. Grunwaldzkiej 54-58, w budynku nr 56 mieścił się Dom Towarowy SEZAM, ok. 1980 r.